An evaluation of technical oral presentation components in engineering / Abdullah Adnan Mohamed - Abdullah Adnan , Mohamed (2020)
This case study evaluates implementation of Technical Oral Presentations (TOP) components in English for Specific Academic Purposes (ESAP) language course for engineering undergraduates at a technical university. The respondents were 310 engineering undergraduates who registered for English Technical Communication (ETC) course and 12 instructors from Universiti Malaysia Pahang. The case study employs Convergent Parallel design to collect data in all four evaluation components of Context, Input, Process and Product (CIPP) Evaluation Model. Two questionnaires were administered in this study. The Questionnaire Set A were distributed to English language instructors teaching English for Technical Communication course while the Questionnaire Set B were distributed among engineering undergraduates who enrolled during September to Dec 2016. Other instruments were semi-structured interviews with six instructors and eight engineering industry stakeholders as well as nine focus group interviews with engineering undergraduates. Eight video clips of engineering undergraduates’ delivering product description presentations were also used as instrument in interview with engineering stakeholders. Findings show that elements of context evaluation such as the ‘relevance’ of ETC course, engineering undergraduates’ level of interest towards TOP and asset and facilities are deemed relevant and conducive. Various difficulties and challenges faced by engineering undergraduates’ in their TOP skills learning were identified and input from instructors teaching the course were also discussed. At least 1/3 of the respondents stated that high anxiety and lack of self-confidence affect their Technical oral Presentation (TOP) performance. Elements of input evaluation such as suitability of content and material for TOP are seen by instructors and engineering undergraduates to be suitable and appropriate for students’ TOP learning. Profiles of instructors teaching TOP showed that they are highly experienced personnel with service duration between five to 21 years. The process evaluation findings illustrate various TOP learning activities occur in classroom and more marks are allocated for content rather than language and delivery skills. However, engineering undergraduates perceive that their instructors give equally high level of emphasis in content, language and delivery skills. Similarly, instructors also viewed that they give highly equal emphasis on these components while teaching TOP. Instructors also adopt various strategies in giving feedback towards engineering undergraduates’ TOP learning. Engineering undergraduates’ perception of instructors’ practices of giving feedback were highly positive. Engineering undergraduates made several suggestions on ways to improve their TOP skills. Product evaluation findings revealed that engineering stakeholders viewed engineering undergraduates’ TOP performance in the video clips as poor, acceptable and good. It is suggested that more training is needed in order to achieve higher competency level. The findings from the Self Perceive Communicative Competent (SPCC) questionnaire revealed that the majority of engineering undergraduates involved in the study perceived their TOP competency to be at moderate level (72.6%) and 22.6% perceived themselves to be in low self-perceived communication competence. Findings also showed that there is no significant difference of self-perceived communication competence among respondents across faculties and between genders. This study proposed a framework known as “PRO-ESATOP” for English specific Academic Purpose (ESAP) and Model of TOP Professionalism for training of Technical Oral Presentation (TOP) skills for engineering undergraduates.